Specifics of the Autobiographical Narrative in “Memoirs” of D. Ovsyaniko-Kulikovskiy - Shekhovtsova, Tatiana (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The article examines the memoir-autobiographical prose of D. Ovsyaniko-Kulikovskiy as an original example of nonfiction literature. The relevance of the work is due to the active study of the theory and history of memoir-biographical prose in domestic and foreign literary studies, as well as the intensive development of contemporary autobiography. The purpose of the study is to identify the specifics of the autobiographical narrative, the peculiarities of the author's self-identification and the construction of the narrator's life story. It is shown that an autobiographical narrative is constructed as a story for others and a story for oneself. Autobiographical memory contains elements of varying degrees of generalization. While maintaining psychophysical identity, the distance between the autocharacter and the narrator is constantly emphasized.As the narrative develops, the narrator's features of a scientist become more and more pronounced, and the narrative shows signs of scientific discourse. "Memoirs" reveals such components of a scientific narrative as description, explanation, analogy, analysis, argumentation, categorization, classification, logical proof, and intertextuality. The supertask performed by the narrator is to characterize the history of his personal and scientific formation as a path to the acquisition of scientific truths and the methodological, basic, and ideological foundations of scientific activity. The narrative also has elements of artistry: complication of the narrative structure, violation of linearity, fictionalization of biographical stories, expressiveness and integrity of images, attention to detail, etc.“Memoirs” by D. Ovsyaniko-Kulikovskiy are a memoir-autobiographical conceptualized narrative subordinated to the author's targeted message. This story combines the features of documentary, scientific and fictional narrative and reveals the author's worldview and scientific credo. At the same time, the inner (perhaps subconscious) core of “Memoirs” actually becomes the process of autocreation of an ideal scientist, which becomes a source of inner satisfaction.